ANALISIS FRAMING MENGENAI PENYEBAB KECELAKAAN KARNAVAL DI PACET MOJOKERTO PADA BERITA ONLINE MENGGUNAKAN MODEL ENTMAN DAN TEORI VAN DIJK - Hidayat Ali Haromaini (Indonesian language and literature education program Majapahit Islamic University, 2023)
Traffic accidents occur due to human factors that do not comply with established regulations. This results in losses for many people, namely traffic jams and loss of property. A carnival accident occurred in Pacet, Mojokerto, because the brakes failed on a tanker truck that was transporting water. This research aims to conduct a framing analysis of the reporting on the causes of the carnival accident in Pacet Mojokerto using the analytical framework. . The framing analysis method uses the Entman models with a qualitative descriptive approach used to determine problem definitions, causes of problems, moral evaluations, recommendations for solutions and through important elements. This research shows that the existence of online media, especially news, can influence people's views or opinions. This has a negative impact on the public's thoughts regarding the carnival accident in Pacet, Mojokerto. Keywords: Framing, Analysis, Accident, Entman, Online News.